ANALISIS PENYELESAIAN SENGKETA PEMILIHAN KEPALA DAERAH DALAM PUTUSAN MAHKAMAH KONTITUSI NOMOR 85/PUU-XX/2022 TERHADAP PEMBENTUKAN BADAN PERADILAN KHUSUS PEMILU DI INDONESIA - Nikmat Ilham; Mexsasai Indra; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The regulations regarding the authority to settle regional election resultsgiven to the Constitutional Court have experienced several polemics. The problemthat arises is that the authority of the Constitutional Court (MK) to resolvedisputes over regional head election results is now permanent. This wasconfirmed in Decision Number 85/PUU-XX/2022 in which the Court stated thephrase